Characterization and abundance of anaerobic ammonia oxidizing (anammox) bacteria in biofilters of recirculating aquaculture systems - Huang, Zhitao; Jiang, Yuli; Song, Xiefa; Hallerman, Eric; Peng, Lei; Dong, Dengpan; Ma, Teng; Zhai, Jieming; Li, Wensheng (BioMed Central Ltd, 2018)
While biofilters are widely used to metabolize ammonia and other wastes in marine recirculating aquaculture systems, the ammonia-oxidizing bacterial and archaeal communities have not been characterized across a diversity of production systems. Using a metagenomics approach, we characterized the ammonia-oxidizing microbiological community of biofilters in a commercial recirculating marine aquaculture system producing hybrid grouper (Epinephelus lanceolatus × E. fuscoguttatus). Cloning and sequencing of the amoA gene showed that nitrifying bacteria included Nitrosomonas europea, N. stercoris, N. cryotolerans, N. eutropha, N. estuarii, eight strains of N. marina, and 15 strains not associated with described species. Nitrifying archaea included eight strains of Nitrosopumilus maritimus, N. koreensis, N. piranensis, N. adriaticus, undescribed congeners, and other undescribed archaea. The species composition of the bacterial and especially the archaeal communities was beyond that yet reported for aquaculture biofilters. While ammonia flux through the respective communities has yet to be estimated, the diverse environmental adaptations of the bacterial and archaeal communities suggest resilience of function under a range of environmental conditions.
Ammonia-oxidizing bacteria and archaea within biofilters of a commercial recirculating marine aquaculture system
Keywords: water quality; growth; Microbial community; recirculating aquaculture system; Hybrid grouper Epinephelus lanceolatus × E. fuscoguttatus; metabarcoding